Theorizing TL esthetics: Forming a femme gaze through yes or no 2.5. Issue 1 (2nd January 2021) - Cheng, Fan-Ting
Abstract: After a long fight, same-sex marriage in Taiwan became legal on 24 May 2019. This milestone does not however address the hegemony that exists inside queer communities, namely, the idea that femininity is the excluded other in gay communities and that femmes are perceived as potential traitors within Taiwanese lesbian society. Such misogynistic ideologies render queer communities less democratic and egalitarian than imagined. This paper coins the term "butchiarchy" as part of an analysis of the Thai lesbian film, Yes or No 2.5 (2015), a box-office hit in Taiwan, in order to reveal the hierarchical structure pervasive within lesbian communities. While reinforcing a butchiarchal norm, the film also mobilizes a femme gaze that plays with the scenes depicting the ambivalent affection between the two butch characters, which echoes the BL (Boys' Love/Yaoi) fever that has swept the popular culture industry in East Asian countries. To distinguish from BL, this paper intends to adopt the term "TL, " as T stands for butch in East Asia, to describe the concept of "Butches' Love, " which differentiates from BL that emphasizes Boys' love. By rethinking terms through which femme is represented as well as experienced, this paper points out how, on the one hand, femme is constantly abjected in order to affirm a constructed lesbian sexuality that problematically recognizes butch as the priori lesbian agent. On the other hand, the femme gazes troubles the butchiarchal surveillance that denies homosexuality in femmes and thus creates a possible scenario that recognizes the operative power of the sub-minority.